Smart Metering Systems and Data Sharing: Why Getting a Smart Meter Should Also Mean Getting Strong Information Privacy Controls to Manage Data Sharing - King,Nancy; Jessen,Pernille W. (International Journal of Law and Information Technology, 2014)
Smart meters are being installed in consumers’ homes as the world moves to the smartgrid of intelligent energy networks. Smart meters are near real-time communication devices that can collect and communicate a vast amount of personal data about each customer’s energy use. Questions about who should have access to such data and for what purposes raise significant consumer privacy concerns about data sharing. Because data sharing facilitates secondary uses of energy use data and is essential for third party access to the data, data sharing is a critical activity that needs to be analysed from an information privacy perspective. This article makes three important contributions. First, it identifies the key privacy and data protection concerns for both the EU and USA consumers related to data sharing in smart metering systems. Second, it provides a comparison of EU and US privacy and data protection law as it applies to smart metering systems, revealing gaps in coverage in both systems. Third, it explains how important privacy concerns related to data sharing are being addressed in the EU and the USA, including specific examples of legislation and self-regulatory mechanisms that have been adopted to protect privacy in smart metering systems. From this comparative analysis, potential privacy-enhancing solutions can be identified. Ultimately it will be up to government regulators and industry to adopt local solutions, but the goal of this article is to encourage adoption of regulatory solutions and industry best practices that are consistent with privacy rights and information privacy principles.
Keywords: Business Law